IMPACT OF GAMIFICATION ON YOUNG LEARNERS AND METHODOLOGICAL EXPERIENCE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The incorporation of gamification in educational settings has gained significant popularity in recent years, especially in language learning contexts. This study aims to examine the impact of gamification on young learners, specifically in their engagement, motivation, and academic performance. The research explores how methodological approaches, such as game-based learning and interactive tasks, influence the learning experiences of children.